Differential transcriptomic responses to heat stress in surface and subterranean diving beetles - Perry G. Beasley-Hall; Terry Bertozzi; Tessa M. Bradford; Charles S. P. Foster; Karl Jones; Simon M. Tierney; William F. Humphreys; Andrew D. Austin; Steven J. B. Cooper (Scientific Reports, 2022)
Abstract Subterranean habitats are generally very stable environments, and as such evolutionary transitions of organisms from surface to subterranean lifestyles may cause considerable shifts in physiology, particularly with respect to thermal tolerance. In this study we compared responses to heat shock at the molecular level in a geographically widespread, surface-dwelling water beetle to a congeneric subterranean species restricted to a single aquifer (Dytiscidae: Hydroporinae). The obligate subterranean beetle Paroster macrosturtensis is known to have a lower thermal tolerance compared to surface lineages (CT max 38 °C cf. 42–46 °C), but the genetic basis of this physiological difference has not been characterized. We experimentally manipulated the thermal environment of 24 individuals to demonstrate that both species can mount a heat shock response at high temperatures (35 °C), as determined by comparative transcriptomics. However, genes involved in these responses differ between species and a far greater number were differentially expressed in the surface taxon, suggesting it can mount a more robust heat shock response; these data may underpin its higher thermal tolerance compared to subterranean relatives. In contrast, the subterranean species examined not only differentially expressed fewer genes in response to increasing temperatures, but also in the presence of the experimental setup employed here alone. Our results suggest P. macrosturtensis may be comparatively poorly equipped to respond to both thermally induced stress and environmental disturbances more broadly. The molecular findings presented here have conservation implications for P. macrosturtensis and contribute to a growing narrative concerning weakened thermal tolerances in obligate subterranean organisms at the molecular level.